(untitled) (One Health Journal of Nepal, 2023)
Introduction: Blood transfusion is the transfer of blood or blood component from donor to recipient. It is a vital and often life-saving procedure which needs proper knowledge and practice of health workers while performing. The main objective of the study was to assess knowledge and practice regarding blood transfusion procedure and its associated factors among healthcare workers working at P.T. Birta City Hospital and Research Center Pvt. Ltd. Methods: Using a multistage sampling technique, a cross-sectional study was conducted involving 126 healthcare workers in Birtamod Municipality. A self-administered questionnaire was employed to assess their knowledge and practice of blood transfusion procedures, with data analysis conducted using SPSS version 23. Results: The study revealed that 96% of healthcare workers exhibited satisfactory knowledge, and 79% demonstrated competent practices in blood transfusion procedures. On average, each health worker conducted 2 blood transfusions per week, with some performing up to 10. The study identified associations between compliance with unit protocol guidelines and knowledge/practices related to blood transfusion, as well as participation in training programs and the level of knowledge about blood transfusion. Conclusions: The majority of healthcare workers exhibited satisfactory knowledge and moderate practices regarding blood transfusion, highlighting the need for targeted refresher training to enhance safe blood transfusion practices, addressing specific areas of deviation.